Genetic variability, genetic advance and correlation in chilli (Capsicum annuum)* - GUPTA, ANAND MOHAN; SINGH, DALJEET; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2011)
A total of 40 hybrids of chilli were evaluated on a field experiment at PAU, Ludhiana during 2005â€“06 to estimate variability, heritability, genetic advance and correlation among fruit yield and component traits. Genotypic and phenotypic co-efficients of variation were high for number of fruits and fruit yield per plant and fruit weight and length. High heritability estimates coupled with high-expected genetic advanceas per cent of men were observed for number of fruits/ plant, fruit yield/ plant, fruit length, fruit weight and capsaicin content. Fruit yield/ plant was positively correlated with number of fruits/ plant and fruit length.Â